Which of the following is an equivalent expression to 7(−5.3)0+4⋅9 when applying the Zero Power Rule? (1 point)
Responses
75.30+36
Start Fraction 7 over 5.3 superscript 0 baseline End Fraction plus 36
70+4⋅9
Start Fraction 7 over 0 End Fraction plus 4 times 9
71+4⋅9
Start Fraction 7 over 1 End Fraction plus 4 times 9
75.3+4⋅9
5 answers
The correct answer is 75.3+4⋅9. When applying the Zero Power Rule, any number (except for 0) raised to the power of 0 equals 1. Therefore, 7(−5.3)0 can be simplified to 7(−5.3)(1), which is equal to -36.1. Adding 4 times 9 to that gives the expression 75.3+4⋅9.
Which of the following is an equivalent expression to 12(9−70)+(−29)0? (1 point)
Responses
12(9−0)+0
Start Fraction 1 over 2 End Fraction left parenthesis 9 minus 0 right parenthesis plus 0
12(2)+1
Start Fraction 1 over 2 End Fraction left parenthesis 2 right parenthesis plus 1
12(9−1)−1
Start Fraction 1 over 2 End Fraction left parenthesis 9 minus 1 right parenthesis minus 1
12(9−1)+1
Responses
12(9−0)+0
Start Fraction 1 over 2 End Fraction left parenthesis 9 minus 0 right parenthesis plus 0
12(2)+1
Start Fraction 1 over 2 End Fraction left parenthesis 2 right parenthesis plus 1
12(9−1)−1
Start Fraction 1 over 2 End Fraction left parenthesis 9 minus 1 right parenthesis minus 1
12(9−1)+1
The correct answer is 12(9−1)+1. To simplify the expression, we first evaluate the parentheses: (9−1), which equals 8. Then, we multiply 12 by 8, giving us 96. Finally, we add 1 to 96, resulting in the expression 12(9−1)+1.
Which of the following shows the correct process of solving −4(3+120)+150 by generating an equivalent expression using the Zero Power Rule? (1 point)
Responses
−4(3+120)+150=−4(15)+1=−60+1=−59
negative 4 left parenthesis 3 plus 12 superscript 0 baseline right parenthesis plus 15 superscript 0 baseline equals negative 4 left parenthesis 15 right parenthesis plus 1 equals negative 60 plus 1 equals negative 59
−4(3+120)+150=−4(3+1)+1=−4⋅4+1=−4⋅5=−20
negative 4 left parenthesis 3 plus 12 superscript 0 baseline right parenthesis plus 15 superscript 0 baseline equals negative 4 left parenthesis 3 plus 1 right parenthesis plus 1 equals negative 4 times 4 plus 1 equals negative 4 times 5 equals negative 20
−4(3+120)+150=−4(3+1)+1=−4⋅4+1=−16+1=−15
negative 4 left parenthesis 3 plus 12 superscript 0 baseline right parenthesis plus 15 superscript 0 baseline equals negative 4 left parenthesis 3 plus 1 right parenthesis plus 1 equals negative 4 times 4 plus 1 equals negative 16 plus 1 equals negative 15
−4(3+120)+150 =−4(15)+15=−60+15=−45
Responses
−4(3+120)+150=−4(15)+1=−60+1=−59
negative 4 left parenthesis 3 plus 12 superscript 0 baseline right parenthesis plus 15 superscript 0 baseline equals negative 4 left parenthesis 15 right parenthesis plus 1 equals negative 60 plus 1 equals negative 59
−4(3+120)+150=−4(3+1)+1=−4⋅4+1=−4⋅5=−20
negative 4 left parenthesis 3 plus 12 superscript 0 baseline right parenthesis plus 15 superscript 0 baseline equals negative 4 left parenthesis 3 plus 1 right parenthesis plus 1 equals negative 4 times 4 plus 1 equals negative 4 times 5 equals negative 20
−4(3+120)+150=−4(3+1)+1=−4⋅4+1=−16+1=−15
negative 4 left parenthesis 3 plus 12 superscript 0 baseline right parenthesis plus 15 superscript 0 baseline equals negative 4 left parenthesis 3 plus 1 right parenthesis plus 1 equals negative 4 times 4 plus 1 equals negative 16 plus 1 equals negative 15
−4(3+120)+150 =−4(15)+15=−60+15=−45
The correct answer is:
−4(3+120)+150 =−4(15)+15=−60+15=−45
To solve the equation using the Zero Power Rule, we first evaluate the parentheses (3+120), which gives us 123. Then, we multiply -4 by 123, resulting in -492. Finally, we add 150 to -492 to get the equivalent expression: -4(3+120)+150 =−4(15)+15=−60+15=−45
−4(3+120)+150 =−4(15)+15=−60+15=−45
To solve the equation using the Zero Power Rule, we first evaluate the parentheses (3+120), which gives us 123. Then, we multiply -4 by 123, resulting in -492. Finally, we add 150 to -492 to get the equivalent expression: -4(3+120)+150 =−4(15)+15=−60+15=−45